The genetic basis of metal hyperaccumulation in plants - Pollard, A; Powell, K; Harper, F; Smith, J (2002)
A relatively small yet diverse group of plants are capable of sequestering metals in their shoot tissues at remarkably high concentrations that would be toxic to most organisms. This process, known as metal hyperaccumulation, is of interest for several reasons, including its relevance to the phytoremediation of metalpolluted soils. Most research on hyperaccumulators has focused on the physiological mechanisms of metal uptake, transport, and sequestration, but relatively little is known regarding the genetic basis of hyperaccumulation. There are no known cases of major genetic polymorphisms in which some members of a species are capable of hyperaccumulation and others are not. This is in contrast to the related phenomenon of metal tolerance, in which most species that possess any metal tolerance are polymorphic, evolving tolerance only in local populations on metalliferous soil. However, although some degree of hyperaccumulation occurs in all members of the species that can hyperaccumulate, there is evidence of quantitative genetic variation in ability to hyperaccumulate, both between and within populations. Such variation does not appear to correlate positively with either the metal concentration in the soil or the degree of metal tolerance in the plant. Studies using controlled crosses, interspecific hybrids, and molecular markers are beginning to shed light on the genetic control of this variation. As molecular physiology provides greater insights into the specific genes that control metal accumulation, we may learn more about the genetic and regulatory factors that influence variable expression of the hyperaccumulation phenotype.